1986
DOI: 10.1007/bf00446061
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease in children of short stature without gastrointestinal symptoms

Abstract: Eighty-seven children with short stature (height more than 2 SD below the mean for age and sex) were investigated by small intestinal biopsy. There was no obvious reason for their growth retardation found by routine examination and they had no gastrointestinal symptoms. Coeliac disease was found in two children and probable coeliac disease in two children. Although the prevalence of coeliac disease was comparatively low in this study of Swedish children with short stature, it emphasizes the fact that coeliac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2
3

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 15 publications
2
24
2
3
Order By: Relevance
“…Previous studies on children with growth failure but without gastrointestinal symptoms have shown a variable incidence of celiac disease (0 to 59.0%) depending on the region where the study was performed (18)(19)(20)(21)(22)(23)(24)(25). All patients with a diagnosis of celiac disease showed an improvement in growth velocity after the introduction of a gluten-free diet, indicating that this parameter would be useful to confirm the correct diagnosis, as also reported by others (19,23,26).…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies on children with growth failure but without gastrointestinal symptoms have shown a variable incidence of celiac disease (0 to 59.0%) depending on the region where the study was performed (18)(19)(20)(21)(22)(23)(24)(25). All patients with a diagnosis of celiac disease showed an improvement in growth velocity after the introduction of a gluten-free diet, indicating that this parameter would be useful to confirm the correct diagnosis, as also reported by others (19,23,26).…”
Section: Discussionsupporting
confidence: 64%
“…Older children may present with recurrent abdominal pain or constipation. In teen-agers the symptoms are often more subtle with anaemia (Mody et al, 2003), late puberty or short stature (Stenhammar et al, 1986). Some cases of childhood CD may present with an acute onset of diarrhoea, dehydration and severely affected general condition, so called celiac crisis (Mones et al, 2007).…”
Section: Symptoms Signs and Complicationsmentioning
confidence: 99%
“…Coeliac disease (CD) is a permanent, genetically determined intolerance to gluten that results in entheropathy and frequent malabsorption in children that may impair final statural growth [4,7,8,27,31,32,43,46]. In fact, after starting a gluten-free diet (GFD), a significant increase in height and weight velocity has been evidenced [5,7,11,13,21,22,30], with weight reaching full catch-up growth in the first year of GFD and height reaching the expected centile after about 2 years [1,42,45].…”
Section: Introductionmentioning
confidence: 98%